Honest Characters in Minangkabau Songket Motifs - Zamil, Ilham (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
Songket woven cloth is one of the traditional cultural objects of the Minangkabau people. Initially, this object could only be worn by traditional officials such as pangulu and bundo kanduang. However, the passage of time has changed the status of use of this songket cloth. Badarai people can also wear it. Even though it has experienced a shift in usage, there is something that has not changed about this songket cloth. The decorative motifs found on songket cloth never change. In fact, there are additional decorative motifs adopted from Rumah Gadang wood carving motifs. The wood carving motif is a symbol of the strength of traditional culture and is also rich in educational character values ​​which symbolize the identity of the Minangkabau people.